Development of Mathematics Teaching Materials Based on the Merdeka Curriculum in Vocational High Schools - Susanti, Reni Dwi; Taufik, Marhan; Effendi, Moh. Mahfud (Department of Mathematics Education University of Muhammadiyah Malang, 2025)
Effective learning is facilitated in large part by teaching modules. Teaching modules of the Merdeka Curriculum serve as useful manuals for educators as they prepare, carry out, and assess their lessons. The goal of this project is to provide teaching modules for mathematics that complement the Merdeka Curriculum's features in vocational high schools (SMK). Teachers of mathematics at SMK participated. Based on instructor input and expert assessment, the created module was determined to be useful and suitable for usage. Comprehensive elements of the training include contextually applicable Pancasila student profiles and prior capabilities. Essential questions, worthwhile learning activities, and comprehensive assessments that include diagnostic, formative, and summative evaluations are all included in this Problem-Based Learning (PBL) method. There are other resources for enrichment and remediation. A high degree of acceptability is shown by the average effectiveness score of 84.625% obtained from teacher replies. It is anticipated that this module will assist educators in carrying out contextualized, relevant learning that is in line with the objectives of the Merdeka Curriculum.